2020
DOI: 10.31744/einstein_journal/2020ao5539
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and semantic validation of an instrument to identify palliative requirements in Portuguese

Abstract: Cross-cultural adaptation and semantic validation of an instrument to identify palliative requirements in Portuguese Adaptação transcultural e validação semântica de instrumento para identificação de necessidades paliativas em língua portuguesa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
1
8
0
1
Order By: Relevance
“…Our main findings showed that the adapted version of the instrument was well adapted to the Brazilian reality, in view of its content validity coefficient. Similar data were verified in another study which contextualized palliative needs in a translated and validated instrument with CVI = 0.94 [ 30 ]. In this sense, content validation allowed for the verification of how many of the included items corresponded to the theoretical construction underlying the instrument, being representative and relevant in covering the phenomenon in question [ 27 ].…”
Section: Discussionsupporting
confidence: 79%
“…Our main findings showed that the adapted version of the instrument was well adapted to the Brazilian reality, in view of its content validity coefficient. Similar data were verified in another study which contextualized palliative needs in a translated and validated instrument with CVI = 0.94 [ 30 ]. In this sense, content validation allowed for the verification of how many of the included items corresponded to the theoretical construction underlying the instrument, being representative and relevant in covering the phenomenon in question [ 27 ].…”
Section: Discussionsupporting
confidence: 79%
“…In recent years, its use has been widespread in different countries. In 2021, it was validated in Chile by Troncoso et al [21], and in Brazil [22]. This tool has been used to identify patient's conditions and palliative care in ve Italian regions [23], and in a Portuguese liver unit [24].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were divided into two groups according to whether palliative care was indicated by the World Health Organization Palliative Needs tools (NECPAL) in its adapted form for Brazilian culture. 18,19 The palliative performance score (PPS) was evaluated for every patient in this study.…”
Section: Data Collectionmentioning
confidence: 99%